Review of RFID and IoT integration in supply chain management - Tan W.C.; Sidhu M.S. (Elsevier Ltd, 2023)
Supply Chain Management (SCM) is increasingly complex and dynamic. Radio frequency identification (RFID) and the Internet of Things (IoT) are expected to play a significant role in fulfilling customer requirements in the supply chain. In this work, the integration of RFID with IoT is called RFID-IoT. RFID-IoT strives to develop automated sensing, seamless, interoperable and highly secure systems by connecting IoT devices through the internet. In this paper, the authors have systematically reviewed the selected literature on the application of RFID-IoT in supply chain management. The contribution of this paper is to review the current state-of-the-art literature and potential trend on the application of RFID-IoT in SCM. There is a need for an in-depth, comprehensive analysis of up-to-date literature to help enhance the management system efficiency, maximize productivity, and minimize cost. This work also explores the current challenges of the reviewed papers in RFID-IoT implementation in the supply chain. The conceptual framework model has been conducted from four major critical SCM perspectives: product manufacturing, shipping and distribution, inventory and retail shop. In the future, this review's highlighted insights and recommendations will hopefully lead to increased efforts toward developing RFID-IoT technologies. 2022